A novel audio steganography technique integrated with a symmetric cryptography: a protection mechanism for secure data outsourcing. (24th September 2021) - PrakashRao, Shirole Rashmi; Jyothi, K.
Data transfer over the internet is a very common process and security of this data is everyone's responsibility. Many techniques are available to secure such confidential data. Among them, cryptography and steganography are two major sub disciplines of information security. The aim of this paper is to maintain the imperceptibility and provide better security. The goals of this paper are to be acknowledged through: the use of variable sample selection method for audio samples - which enhances the security with better audio quality; and deploying one of the most secure algorithms - blowfish. It is used to secure data from eavesdropping. Performance of proposed work is compared with the traditional LSB algorithm for audio. The proposed system is the best approach for enhancing the security and retaining the good quality of the cover object.